Electrical Energy Storage Solutions: Powering the World of Tomorrow - Maytham Abdulzahra Majeed; Zainalabden A. Ibrahim; Dhuha jalal kamil (Peerian Journals Publishing, 2024)
In an era marked by relentless technological advancements and burgeoning global energy demand, the role of electrical energy storage solutions has become paramount. This article delves into the world of electrical energy storage, exploring its multifaceted significance in shaping a sustainable and electrified future.The need for efficient energy storage solutions has never been more evident. As our societies grow more interconnected and energy-dependent, the demand for reliable power supply continues to surge. Traditional energy grids, though robust, face challenges in accommodating intermittent renewable energy sources and addressing peak demand. Electrical energy storage emerges as the linchpin that bridges these gaps, ensuring uninterrupted power supply, optimizing grid performance, and facilitating the integration of renewable energy sources
Keywords: Electrical energy storage; Battery technology; Grid-scale energy storage